Role Play as an Active Learning Techniques in Improving Speaking Skill of Grade 7 Students at MTs Al-Huda Gorontalo - Wahyudin A.R. Latoko; Moh. Syahrun Ibrahim; Sri Agriyanti Mestari; Rasuna Rasid Talib; Zulkifli Tanipu (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This study aimed to investigate the effectiveness of the Role Play technique as an active learning strategy in improving the speaking skills of seventh-grade students at MTs Al-Huda Gorontalo. The research employed a quantitative approach using a pre-experimental one-group pre-test and post-test design. The participants of the study were 24 students of Class VII-B in the 2024/2025 academic year. Data were collected through speaking tests administered before and after the treatment. The speaking assessment covered fluency, pronunciation, vocabulary, grammatical accuracy, and comprehensibility using a rubric adapted from Brown (2004). The treatment was conducted in six meetings through structured, semi-guided, and open-ended role play activities based on daily communication contexts. The results showed that students’ speaking skills improved significantly after the implementation of the Role Play technique. The mean score increased from 48.55 in the pre-test to 63.36 in the post-test. In addition, students became more confident, active, and fluent in expressing ideas orally. The paired sample t-test indicated that the improvement was statistically significant at the 0.05 level. Therefore, Role Play was found to be effective in improving students’ speaking skills and creating a more interactive and communicative learning environment.